Effect of Thermal Overload Relay (TOR) as Overheating Protection on BSR-10 Type Biofuel Pelletizer Molding Machine - Saragih, Yuliarman; Hiermy, Ulpen (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
BSR-10 type biofuel pellet forming machine is widely used in renewable energy industry to produce high quality biofuel pellets. However, prolonged operation and heavy loads on these engines can cause their temperature to rise excessively and potentially damage the electric motors. To overcome this problem, this study aims to investigate the effect of using a Thermal Overload Relay (TOR) as a protection against overheating in a BSR-10 type biofuel pellet forming machine. This research involves measuring temperature and engine performance when operated with and without TOR. Motor temperature and engine ambient temperature are observed and recorded during normal operation and heavy load situations. In addition, engine performance in terms of rotational speed, energy consumption and pellet production were also evaluated with and without TOR. The results showed that the use of TOR significantly reduced the motor temperature in the BSR-10 type biofuel pellet forming machine. When given a heavy load, the engine that is protected by TOR shows a more stable and controlled temperature compared to the engine without TOR. In addition, TOR-equipped machines also show improvements in overall performance, including more stable rotational speeds, more efficient energy consumption and consistent pellet production. In conclusion, the use of Thermal Overload Relay (TOR) as protection against overheating in the BSR-10 type biofuel pellet forming machine is effective in controlling motor temperature, improving engine performance, and preventing damage caused by excess temperature. This research provides a better understanding of the use of TOR in the context of biofuel pelletizing machines and can provide useful guidance to the renewable energy industry in improving the operational efficiency and reliability of their machines..